2021
DOI: 10.3390/en14217250
|View full text |Cite
|
Sign up to set email alerts
|

NOx Emission of a Correlation between the PEMS and SEMS over Different Test Modes and Real Driving Emission

Abstract: The aim of this study is to verify the reliability of NOx emissions measured using Smart Emissions Measurement System (SEMS) equipment in comparison with the NOx emissions measured using certified Portable Emissions Measurement System (PEMS) equipment. The SEMS equipment is simple system, and it is less expensive than the PEMS equipment, as it comprises an On-Board Diagnostics (OBD) signal from the test vehicle and a NOx sensor. The SEMS equipment based on low-cost sensors has an advantage of building big data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The CO 2 was calculated based on the fuel carbon-hydrogen ratio and the fuel flow rate. Studies have shown that the results are well comparable with PEMS [41].…”
Section: Testingsupporting
confidence: 63%
“…The CO 2 was calculated based on the fuel carbon-hydrogen ratio and the fuel flow rate. Studies have shown that the results are well comparable with PEMS [41].…”
Section: Testingsupporting
confidence: 63%
“…In the case of NO x emissions, although they are not as accurate as PEMS, readily available production NO x sensors are considered as a valuable source of information. 59,60 The benefits and applications of vehicle emissions models are clear and have been widely addressed. In the foreseen connected framework with on-board emission monitoring requirements, 61,62 assessing whether realworld data alone (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of N O x emissions, although they are not as accurate as PEMS, readily available production NO x sensors are considered as a valuable source of information. 59,60…”
Section: Introductionmentioning
confidence: 99%